THE RELATIONSHIP BETWEEN TTM (TIME TO MARKET) TOOL AND EVALUATING THE PERFORAMNCE OF PRODUCTS’ LAUNCHING PROCESS: A CASE STUDY OF ORANGE JORDAN - Rifat O. Shannak; Amal AL-Masri (European Scientific Journal, ESJ, 2012)
The objective of this research is to evaluate and study the relationship between Time To Market (TTM) tool and the performance of the launching process of Orange (Mobile Company) products and services. The type of research design is modeled as case study; it relies on secondary information and primary data. The research has been conducted through interviews .The conduction and analysis of the interviews follow a methodology called (general interview guide approach). In addition, a sample of Orange products and services has been selected. The product list was filtered taking into consideration the existence of products pre and post the implementation of the TTM. The Willcoxon statistical test was used to test research hypotheses and to analyze the data. The research major conclusions are that TTM tool effectively contributes in products and services launching process and also creates an enabling environment for creativity and innovation. Information systems that support the core business and which is thought to be strategically important in product launching process should be customized. In addition, albeit TTM evaluation process is deemed important, more focused measures and methods for evaluation are needed. The research has proposed several recommendations; of which the most important are: TTM internal process needs to be improved and enhanced since the sharing of lessons learned by employees and TTM users is required and more weight should be given to planning phase in the launching process.